Implementasi Modul Pembelajaran Bidang Studi Al Qur’an Hadis Dalam Meningkatkan Pemahaman Siswa Kelas VII MTs Swasta Tarbiyah Waladiyah Pulau Banyak - Maulida Maulida; Irmayanti Br Sembiring; Ratna Aprilla Sinaga (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2021)
The objectives of this research are 1). To find out the use of student learning modules in Al-quran Hadith subjects for grade VII students of Madrasah Tsanawiyah Private Tarbiyah Waladiyah Pulau Banyak. 2). To determine the ability of students to understand the material in the field of study of the Qur'an Hadith in class VII Madrasah Tsanawiyah Private Tarbiyah Waladiyah Pulau Banyak. 3). To find out whether the use of student learning modules can improve students' ability to understand the subject matter of the Qur'an Hadith for grade VII students of Madrasah Tsanawiyah Private Tarbiyah Waladiyah Pulau Banyak. The method used in this research is the classroom action research method (CAR), which is action research carried out as a problem-solving strategy by utilizing real actions and then reflecting on the results of the action. The results of these actions and reflections are used as a step in selecting the next action according to the problems faced. Problem Identification: 1). Grade VII MTs students. Private Tarbiyah Waladiyah Tanjung Pura who received learning using the Teaching Module approach showed a significantly better understanding of Al-Quran Hadith material compared to students who received regular learning. This can be seen from the average score of students' understanding abilities in the field of study of the Qur'an and Hadith; 2). Understanding ability of students of class VII MTs. Private Tarbiyah Waladiyah Pulau Banyak can be done by applying the Teaching Module; 3). There is a significant relationship between increasing comprehension ability through the teaching module learning model in MTs. Private Tarbiyah Waladiyah Pulau Banyak. 4). The attitude of students during learning Al quran Hadith looks good, namely students have the enthusiasm to participate in learning activities in class, students look more enthusiastic in learning activities and communication that occurs during the learning process in class is effective, in connection the communication goes in two directions, namely from teacher to student and vice versa from students to teachers; 5). The activities of students who receive learning using the Teaching Module are more active in learning in the classroom and students who receive the Teaching Module are more active in improving students' understanding abilities, and students are also more daring to raise or ask questions to the teacher, and are more creative in solving the problems given, so that the understanding ability of MTs students. Private Tarbiyah Waladiyah Pulau Banyak can be increased through the application of the Teaching Module model.